Regulation, Fiction, and Flow - de Sousa, Ronnie (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
Chapter 11 contains two primary topics, the regulation of emotions and questions arising from the power of music to arouse, express, or represent emotions. After some brief remarks about emotion regulation and a speculative thought about emotions in response to fiction, I raise some doubts about the discussion of “flow” in connection with listening to as opposed to performing music.